Angiotensin‐Converting Enzyme Inhibitors or Angiotensin Receptor Blockers Use and COVID‐19 Infection Among 824 650 Patients With Hypertension From a US Integrated Healthcare System - Jaejin An; Rong Wei; Hui Zhou; Tiffany Q. Luong; Michael K. Gould; Matthew T. Mefford; Teresa N. Harrison; Beth Creekmur; Ming‐Sum Lee; John J. Sim; Jeffrey W. Brettler; John P. Martin; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Previous reports suggest that the use of angiotensin‐converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) may upregulate angiotensin‐converting enzyme 2 receptors and increase severe acute respiratory syndrome coronavirus 2 infectivity. We evaluated the association between ACEI or ARB use and coronavirus disease 2019 (COVID‐19) infection among patients with hypertension. Methods and Results We identified patients with hypertension as of March 1, 2020 (index date) from Kaiser Permanente Southern California. Patients who received ACEIs, ARBs, calcium channel blockers, beta blockers, thiazide diuretics (TD), or no therapy were identified using outpatient pharmacy data covering the index date. Outcome of interest was a positive reverse transcription polymerase chain reaction test for COVID‐19 between March 1 and May 6, 2020. Patient sociodemographic and clinical characteristics were identified within 1 year preindex date. Among 824 650 patients with hypertension, 16 898 (2.0%) were tested for COVID‐19. Of those tested, 1794 (10.6%) had a positive result. Overall, exposure to ACEIs or ARBs was not statistically significantly associated with COVID‐19 infection after propensity score adjustment (odds ratio [OR], 1.06; 95% CI, 0.90–1.25) for ACEIs versus calcium channel blockers/beta blockers/TD; OR, 1.10; 95% CI, 0.91–1.31 for ARBs versus calcium channel blockers/beta blockers/TD). The associations between ACEI use and COVID‐19 infection varied in different age groups (P‐interaction=0.03). ACEI use was associated with lower odds of COVID‐19 among those aged ≥85 years (OR, 0.30; 95% CI, 0.12–0.77). Use of no antihypertensive medication was significantly associated with increased odds of COVID‐19 infection compared with calcium channel blockers/beta blockers/TD (OR, 1.32; 95% CI, 1.11–1.56). Conclusions Neither ACEI nor ARB use was associated with increased likelihood of COVID‐19 infection. Decreased odds of COVID‐19 infection among adults ≥85 years using ACEIs warrants further investigation.